Metacognitive Strategy for Arabic Writing among Students in Arabic Departement - Kafi, Fina Aunul; Wargadinata, Wildana; Mubaligh, Ahmad (Institut Agama Islam Negeri Curup, 2024)
This study aims to delve deeper into the understanding of metacognitive strategies in students’ Arabic writing. Metacognitive strategies in Arabic writing are crucial because this language is not their mother tongue in their habits. Moreover, there are substantial differences between sounds and writing symbols in Arabic that have distinct characteristics compared to foreign languages, like European languages in particular. Using the non-experimental method, we used 40 samples of mid-year students studying in the Arabic Language Study Program. They are given instructions to write an Arabic essay within the allotted time. We tested the data from the questionnaire using statistical descriptive and Pearson's correlational techniques. Meanwhile, the results of student essay writing were assessed according to the criteria of Holly L. Jacob. Through statistical descriptive tests, it was found that the average use of metacognitive strategies (MS) was 71.70, while the average essay score (ES) was 80.60. Based on Pearson's correlation test, it was found that Sig. (2-tailed) MS and ES were 0.078 and Pearson correlation was 0.282. Through these calculations, it shows that there is no correlation between the x and y variables, positive correlation values, and weak degrees. Meanwhile, based on the observation of the assessment results, it shows that there are repeated errors in organizing, language use, and writing techniques. These findings show that MS that is good at writing Arabic without adequate writing knowledge will produce less quality writing. And vice versa, adequate author knowledge without a good MS will result in less structured and coherent writing.